The influence of general and static endurance of highly qualified athletes on the effectiveness of competitive activity in sailing races on YaL-6 - Paramzin, V. B.; Pugachev, I. Yu.; Raznovskaya, S. V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to reveal the structure of the physical readiness factors of highly qualified athletes that affect the effectiveness of competitive activity, as well as to determine the most important general physical qualities of developing the ability to resist fatigue in sailing races on Y?L-6.Methods and structure of the study. The scientific work was attended by 16 members of the team of the Naval Institute of Radio Electronics. A.S. Popov (St. Petersburg), divided into two mixed (with a high and low level of endurance) crew. Endur-ance level (high, low) was determined by 1 km cross-country and Cooper's test. To determine the degree of influence of the most important general physical qualities (general and static endurance), during the control training, a comparative experi-ment was conducted using a blank method for self-assessment of the ability to resist fatigue.Results and conclusions. Four generalized factors were identified with a total dispersion of indicators: the first - indicators of general and static endurance amounted to 33%, the second "professional sailing readiness" - 29%, the third "functional state and physical development" - 20%, the fourth - indicators of "speed" - 17 %. According to the results of the blank method of self-assessment and heart rate, significant differences in the ability to resist fatigue were established. In athletes with a low level of fatigue, they appeared already by the second hour of the race, and in athletes with a high level, they were not observed until the end of the race. Significant indicators are: vital capacity, cross training, maximum oxygen consumption, static endur-ance. Thus, the level of endurance according to the result in running for 1 km should not be lower than 204 seconds, in the Cooper test - not lower than 3.3 km, which, in turn, will positively affect the stability of the psychophysiological functions of the body and performance during sailing races.